Pengunaan Media Gambar dalam Meningkatkan Minat Baca Peserta Didik Kelas V di MI Raudlatul Wathoni - Suhaibatul Aslamiah (Al-Gafari : Manajemen dan Pendidikan, 2024)
Learning media is one component in education that determines the success of the learning process. So that educators need to understand the use of learning media by adjusting the material to be taught. The purpose of the study was to determine the use of image media as a medium to foster students' interest in reading. The data collection techniques used were observation, questionnaires and documentation, while the data analysis was data reduction, data presentation and drawing conclusions. The results of this study prove that in order to increase students' interest in reading, using image media gets better results compared to learning that only relies on one-sided conversations. Students generally aged between 8-10 years are very happy with image media, especially if the images used as media are full of attractive colors. Image media can clarify a problem, in any field and for any age level, so that it can prevent misunderstandings. Image media is easy to get and use without the need for special equipment. The hypothesis that can be formulated in this study is that the use of image media as a learning medium has a positive effect on children's interest in reading at MI Raudlatul Wathoni. Looking at the results of the research conducted by researchers on grade 5 students at MI Raudlatul Wathoni, through picture story books media is very suitable to be used as a medium to increase students' interest in reading. Of the 20 samples used in the study, around 35% felt happy reading using picture story books. while those who were very happy were around 55%, less happy 15%, not happy around 0% and those who were very unhappy as much as 0%.